Enhancing the selectivity of hydrocarbons during the Kolbe electrolysis of biomass-derived short-chain carboxylic acids by anionic surfactants. Issue 11 (16th May 2022) - Lang, Lin; Li, Yanbing; Lam, Jason Chun-Ho; Ding, Yingna; Yin, Xiuli; Wu, Chuangzhi
Abstract : Different mechanisms of selective electrochemical decarboxylation of acetic acid and butyric acid in aqueous solution and at room temperature. Abstract : Kolbe electrolysis of biomass-derived carboxylic acids into biofuels or chemicals represents a promising approach for the valorization of sustainable carbon sources, but selectively producing hydrocarbon products remains a great challenge in aqueous solution, especially for C2 –C4 short-chain carboxylic acids (SCCAs). In the current work, significant increases in hydrocarbons were observed by doping a trace amount of an eco-friendly anionic surfactant (sodium dodecyl sulfate, SDS). We investigated the selective electrochemical decarboxylation of acetic acids and butanoic acids in aqueous solutions and at room temperature, following the principles of green chemistry. SDS provided a more hydrophobic layer on the Pt electrode surface that helps to protect organic species or radicals from water, which could improve the selectivity of hydrocarbons for the aqueous SCCAs solutions. However, the mechanism of selectivity improvement was different for the two common SCCAs. The SDS layer promoted the adsorption and retention of propyl radicals for butyric acid solutions and improved its conversion and dimerization to yield hexane, but the bulky propyl radicals also easily depart from the hydrophobic layer to become more propene. For acetic acids, however, the smaller methyl radical could be better protected in the hydrophobic SDS layer from reacting with the hydrophilic species in the aqueous phase; thus, the methanol product was inhibited, and OER reaction was promoted. This study provides a significant advancement to produce green hydrocarbons by improving the SCCAs application of aqueous Kolbe electrolysis.